Price Competition with Information Disparities in a Vertically Differentiated Duopoly - Alberto Cavaliere (Fondazione Eni Enrico Mattei (FEEM), 2004)
In this paper we extend the model of vertical product differentiation to also consider information disparities about the extent of quality differences. Equilibrium prices turn out to depend not only on the share of informed consumers but also on uninformed consumers beliefs about quality differences. If uninformed consumers overestimate vertical differentiation, informed consumers exert a positive externality on the purchasers of the high quality good as its price decreases when the share of informed consumers decreases. Considering also that the price of the low quality good increases with the share of informed consumers, higher prices can-not signal high quality goods. If uninformed consumers have pessimistic beliefs and underestimate the extent of vertical differentiation, informed consumers can exert a positive externality on firms. In fact either market demands are inelastic to prices and the profits of the high quality firm increase with the share of informed consumers or market demands are elastic to prices and the profits of both firms increase with the share of informed consumers. In the latter case prices are also equal to those that would prevail with perfect information. In the case of optimistic consumers we can then find some theoretical foundation concerning the fact that information undermines brand, while with pessimistic consumers we can explain demand collapses and insensitivity to price changes due to consumer suspicions about product quality.
Keywords: L13; L15; 330; Vertical product differentiation; Asymmetric information; Quality uncertainty; Prices as quality signals; Produktdifferenzierung; Asymmetrische Information; Duopol; Preiswettbewerb; Produktqualität; Signalling